Lateral hypothalamic orexin and melanin-concentrating hormone neurons provide direct input to gonadotropin-releasing hormone neurons in the human - Skrapits, Katalin; Kanti, Vivien; Savanyú, Zsófia; Maurnyi, Csilla; Szenci, Ottó; Horváth, András; Borsay, Beáta Á.; Herczeg, László; Liposits, Zsolt; Hrabovszky, Erik (Frontiers in Cellular Neuroscience, 2015)
Hypophysiotropic projections of gonadotropin-releasing homone (GnRH)-synthesizing neurons form the final common output way of the hypothalamus in the neuroendocrine control of reproduction. Several peptidergic neuronal systems of the medial hypothalamus innervate human GnRH cells and mediate crucially important hormonal and metabolic signals to the reproductive axis, whereas much less is known about the contribution of the lateral hypothalamic area to the afferent control of human GnRH neurons. Orexin (ORX)- and melanin-concentrating hormone (MCH)-synthesizing neurons of this region have been implicated in diverse behavioral and autonomic processes, including sleep-awakeness, feeding and other functions. In the present immunohistochemical study, we addressed the anatomical connectivity of these neurons to human GnRH cells in post-mortem hypothalamic samples obtained from autopsies. We found that 38.9±10.3% and 17.7±3.3% of GnRH-immunoreactive (IR) perikarya in the infundibular nucleus (INF) of human male subjects received ORX-IR and MCH-IR contacts, respectively. On average, each 1 mm segment of GnRH dendrites received 7.3±1.1 ORX-IR and 3.7±0.5 MCH-IR axo-dendritic appositions. Overall, the axo-dendritic contacts dominated over the axo-somatic contacts and represented 80.5±6.4% of ORX-IR and 76.7±4.6% of MCH-IR inputs to GnRH cells. Based on functional evidence from studies of laboratory animals, the direct axo-somatic and axo-dendritic input from ORX and MCH neurons to the human GnRH neuronal system may convey critical metabolic and other homeostatic signals to the reproducive axis. In this study, we also report the generation and characterization of new antibodies for immunohistochemical detection of GnRH neurons in histological sections.